The Effectiveness of Varying Plyometric Training Intensities in Improving Punching Force and Muscular Fitness in Adolescent Boxers - Singh, Shailendra; Deori, Lata Apara; Chetry, Purnima; Manamkandath, Mohamed Prince; Astuti, Yuni; Saha, Sohom; Khati, Awesh (Physical Education Theory and Methodology, 2025)
Background. The sport of boxing requires a great deal of explosive strength, particularly punching force and muscular fitness, which are crucial during adolescence due to the rapid development of neuromuscular systems. Plyometric training is known to enhance certain physical attributes. However, limited comparative research exists on the effectiveness of different plyometric training intensities in adolescent boxers. Objectives. The study aimed to examine and assess the impact of high- and low-intensity plyometric training protocols on the punching force and muscle fitness of teenage male boxers. Materials and Methods. Thirty adolescent male boxers, aged 13-17 years, each with at least three years of training experience, were chosen at random to be divided into three groups: Low-Intensity Plyometric Training (LIPT), High-Intensity Plyometric Training (HIPT), and an Active Control Group (ACG). The LIPT and HIPT groups engaged in an 8-week plyometric program conducted thrice weekly, with progressive overload, while the ACG continued with their standard boxing training routines. Pre- and post-intervention assessments included punching force, upper and lower body power, and muscular endurance, measured through validated sport-specific tests. Statistical analysis involved paired t-tests, ANOVA, and Bonferroni post-hoc tests. Results. Both the LIPT and HIPT groups demonstrated statistically significant improvements (p < .001) across all measured variables, while the ACG exhibited no substantial changes. The HIPT group achieved the highest gains, with punching force increasing by 17.54%, muscular endurance by 31.77%, lower body power by 21.02%, and upper body power by 9.96%. Effect sizes were large (η²p ≥ .65), indicating strong treatment effects. Conclusions. Plyometric training, especially at high intensities, significantly enhances punching force and muscular fitness in adolescent boxers. These findings support the integration of progressively overloaded plyometric exercises into youth boxing training programs, providing a scientifically grounded approach to improving performance during a critical developmental phase.